The Acquisition of English Prepositional Verbs by Jordanian EFL Learners at Al-Isra Private University - Mukallaluh, Saleh (Jordan Journal of Educational Sciences, 2005)
The present study investigated the acquisition of English prepositional verbs by 76 Jordanian EFL learners at Al-Isra Private University, Amman – Jordan. The study was intended to specifically find out whether the null – prep phenomenon is significantly observed in the Jordanian EFL learners’ interlanguage grammar and whether the development of preposition stranding and preposition pied – piping in wh-questions and relative clauses would differ. A task involving grammaticality judgement and correction of individual sentences was given to the study subjects. Eight pairs of verb + preposition (V + P) were tested in three sentence types: declaratives, related wh-questions and relative clauses, each with the obligatory preposition omitted. Thus, the corpus consisted of 24 targeted sentences. The study results indicate that the rise in the use of both preposition stranding and preposition pied – piping and the fall in the rate of the null – prep phenomenon occur more in instances of wh – questions than those of relative clauses across the three groups of proficiency. Additionally, and more importantly, the null – prep occurs rather similarly in both arguments and adjuncts. Interestingly enough, the present study results receive support from the studies reported in the literature and reflect how prepositional verbs are taught in Jordanian EFL classrooms.(